Smartphone nation : building digital boundaries when offline isn't an option - Regehr, Kaitlyn (The Dial Press, an imprint of Random House, 2025)
This book examines the challenges of raising children in a digital environment shaped by smartphones, social media, and artificial intelligence. Regehr reviews research on the risks and impacts of online content, explores how algorithms influence information consumption, and outlines strategies for developing healthy digital habits within families. Framed as a practical guide for parents, the work emphasizes digital literacy, informed decision-making, and approaches to helping children navigate technology rather than avoid it.